Human-engineered auricular reconstruction (hEAR) by 3D-printed molding with human-derived auricular and costal chondrocytes and adipose-derived mesenchymal stem cells. (3rd December 2021) - Landau, Shira; Szklanny, Ariel A; Machour, Majd; Kaplan, Ben; Shandalov, Yulia; Redenski, Idan; Beckerman, Margarita; Harari-Steinberg, Orit; Zavin, Janet; Karni-Katovitch, Oryan; Goldfracht, Idit; Michael, Inbal; et al.
Abstract: Microtia is a small, malformed external ear, which occurs at an incidence of 1–10 per 10 000 births. Autologous reconstruction using costal cartilage is the most widely accepted surgical microtia repair technique. Yet, the method involves donor-site pain and discomfort and relies on the artistic skill of the surgeon to create an aesthetic ear. This study employed novel tissue engineering techniques to overcome these limitations by developing a clinical-grade, 3D-printed biodegradable auricle scaffold that formed stable, custom-made neocartilage implants. The unique scaffold design combined strategically reinforced areas to maintain the complex topography of the outer ear and micropores to allow cell adhesion for the effective production of stable cartilage. The auricle construct was computed tomography (CT) scan-based composed of a 3D-printed clinical-grade polycaprolactone scaffold loaded with patient‐derived chondrocytes produced from either auricular cartilage or costal cartilage biopsies combined with adipose-derived mesenchymal stem cells. Cartilage formation was measured within the construct in vitro, and cartilage maturation and stabilization were observed 12 weeks after its subcutaneous implantation into a murine model. The proposed technology is simple and effective and is expected to improve aesthetic outcomes and reduce patient discomfort.